2015
DOI: 10.1080/00140139.2015.1043356
|View full text |Cite
|
Sign up to set email alerts
|

Task variation during simulated, repetitive, low-intensity work – influence on manifestation of shoulder muscle fatigue, perceived discomfort and upper-body postures

Abstract: Work-related musculoskeletal disorders are increasing due to industrialisation of work processes. Task variation has been suggested as potential intervention. The objectives of this study were to investigate, first, the influence of task variation on electromyographic (EMG) manifestations of shoulder muscle fatigue and discomfort; second, noticeable postural shoulder changes over time; third, if the association between task variation and EMG might be biased by postural changes. Outcome parameters were recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 53 publications
1
22
0
1
Order By: Relevance
“…The cranial shift in the standardised protocols might reflect the tendency to elevate the shoulder complex in order to relief the constantly active shoulder muscle parts (e.g., Luger et al, 2015;Samani et al, 2010). This explanation may support the psychophysical findings somewhat, as reported in the previous paragraph.…”
Section: Autonomysupporting
confidence: 67%
See 1 more Smart Citation
“…The cranial shift in the standardised protocols might reflect the tendency to elevate the shoulder complex in order to relief the constantly active shoulder muscle parts (e.g., Luger et al, 2015;Samani et al, 2010). This explanation may support the psychophysical findings somewhat, as reported in the previous paragraph.…”
Section: Autonomysupporting
confidence: 67%
“…The electrode rows were placed in line with the muscle fibre directions of both muscles with an inter electrode distance (IED) of 15 mm (for details, see Luger et al, 2015). Muscle activity of the right Deltoid pars Clavicularis, Acromialis and Spinalis was measured with a bipolar EMG configuration (IED 20 mm) according to the Seniam guidelines (Hermens et al, 2000).…”
Section: Electromyographymentioning
confidence: 99%
“…Although there is general agreement that human cognitive processes from an integrative component of computerassisted interventional technologies, we still do not know enough about how human performance and decision making is affected by these technologies [34]. The pressing need for research in this domain reaches far beyond the realms of workflow analysis and task models (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Increased variation in biomechanical exposures may be obtained by changing the content of individual tasks, by changing the time pattern of these tasks, or by introducing new tasks. Examples of interventions include the design of workstations or other equipment, introduction of additional breaks (Galinsky et al, 2007;Henning, Jacques, Kissel, Sullivan Alteras-Webb, 1997;Luger, Bosch, Hoozemans, De Looze, & Veeger, 2015), re-arrangement of breaks through the working day (Balci & Aghazadeh, 2003;Dababneh, Swanson, & Shell, 2001), and job rotation (Luger, Bosch, Hoozemans, Veeger, & De Looze, 2016;Riss en, Melin, Sandsj€ o, Dohns, & Lundberg, 2002;Roquelaure et al, 1997). A recent review of studies investigating biomechanical exposure variation by Luger, Bosch, Veeger, and De Looze (2014) concluded that the evidence for positive effects of increased exposure variation on indicators of fatigue is limited.…”
Section: Introductionmentioning
confidence: 99%